"It Just Got Real:" Navigating the Affordances and Constraints of School-Based Learning in a Mathematics-Specific Induction Program. (3rd May 2017) - Ticknor, Anne Swenson; Schwartz, Catherine Stein
ABSTRACT: As beginning teachers encounter their first classrooms, they struggle to enact curriculum and negotiate expectations of local context with their visions of "good teaching." This article is a qualitative research design utilizing interview data and narrative analysis to examine the storied experiences of beginning teacher participants navigating the first year of teaching. The authors explore how beginning teachers can be supported in agentically negotiating personal goals and professional contexts. The authors describe ways three first-year elementary teachers' mathematics teaching was supported and constrained by local schools and an external university-based mathematics-specific induction program, Learning Agency by Understanding how to Navigate Context and Harness Vision (LAUNCH), into mathematics teaching. Some supports provided by the induction program can be and sometimes were provided by local school contexts whereas other supports were possible because of the external nature of the program.